El derecho al agua: el movimiento de las resistencias unidas contra la cervecera Constellation Brands (2022)
On March 21 and 22, 2020 a public consultation took place in Mexicali, where the continuation of the transnational brewery Constellation Brands in the region was considered. In this consultation it was possible to vote for one of the following options: Yes to the brewery or No to the brewery, where No won with an astonishing 76% of the votes (29 793). The case of the resistance raises some questions that will be addressed in the research: What has been the process and paths taken by the resistance in defense of water? What determined the success of the resistance (expressed in the rejection of the brewery in the public consultation)? The research analyzes the case of the united resistance in defense of water against the transnational brewery Constellation Brands. The research is qualitative research with a significant ethnographic component, where process tracing is used to analyze the resistance since the beginning of 2017 and until April 2020. The main argument of this research is that the case analyzed is a case of decolonial critical theory of resistance. Furthermore, the paper explains that three factors were crucial for the triumph of the resistance with the rejection of the brewery in the public consultation: the joint legal and protests paths, the union of groups in one resistance movement and the triumph of the left wing in the federal government: These factors can be seen as INUS (insufficient but necessary causes, that jointly lead to the outcome).